Young farmers in “The New World of Work”: The contribution of new media to the work engagement and professional identities - İlkay Unay-Gailhard; Mark A. Brennan (Rural Sociology, 2023)
This study aims to explore the contribution of “The New World of Work” to farming, a career often viewed as unattractive among youth, and, as highlighted by the “young farmer problem” in the literature. This paper draws upon research on the role of “new ways of working” in work engagement and farmer identity among young farmers. A mixed-method approach is used based on data from two Mediterranean Islands, Crete and Cyprus. Based on the polymedia- new theory of digital media, the study focuses both on new media use and new media engagement for work-related tasks. Our findings highlight that the “The New World of Work” is an important phenomenon for initiating positive change toward cohesive social-self in a career (subjective perception of a farming career concerning others). However, we identified binary terms used by farmers when explaining conflicts between cohesive self-concept (expression of a strong sense of self regarding their farming career) and social-self in a career. The study concludes that the duality between career self-concepts and social-self still holds patterns even among young generation farmers, regardless of their integration level to new media.
Keywords: 300